Pelanggaran Hak Asasi Manusia Terhadap Anak-Anak Dan Pertanggungjawabannya Menurut Hukum Internasional - Elco, Urlialy; Wattimena, Josina Augustina Yvonne; Tuhulele, Popi (Faculty of Law, Universitas Pattimura, 2023)
Introduction: A total of 169 of the total 181 ILO member states have ratified Convention No. 182 since its adoption in 1999. This means that these countries have committed to take immediate and effective action to prohibit and eliminate all forms of worst child labour. One of the ILO member countries that are committed is the Philippines.Purposes of the Research: The purpose of this study is to analyze and find out that human rights violations against children in the Philippines can be classified as crimes against humanity, to analyze and determine the responsibility of the perpetrators according to international law and, as one of the requirements in completing studies at the law faculty.Methods of the Research: The method used is a normative juridical research method with an analytical descriptive type, a process to find rules, principles, and legal doctrines in order to answer the legal information at hand.Results of the Research: The results showed that Human Rights Violations in the Philippines can be classified as human crimes because the types of crimes that can be classified as crimes against humanity, are: murder, extermination, slavery, deportation, exploitation and other inhumane acts committed against the civilian population, or persecution. on political, racial or religious grounds in the commission of or in connection with crimes within the jurisdiction of the Court. Because exploitation is a type of crime that can be qualified as a crime against humanity, the Human Rights Violations in the Philippines can be classified as human crimes. Perpetrators of sexual exploitation of children in the Philippines can be held accountable under international law because in international law perpetrators of sexual exploitation of children have violated human rights, especially regarding the Convention on the Rights of the Child. In addition, the Philippines has established special rules regarding human trafficking as stipulated in the Republic of Indonesia Law Number 9208 or known as the Anti-Trafficking Law in 2003.